EQUALITY, SEXUALITY AND TAKING RIGHTS SERIOUSLY - Karthy Govender (Obiter, 2022)
Minister of Home Affairs v Fourie 2006 3 BCLR 355 (CC) is, from a legal and constitutional perspective, relatively uncomplicated and the conclusion almost inevitable, given the explicit terms of the Constitution. However, the directive to Parliament to regulate gay and lesbian unions in a manner consistent with dignity, caused a national outcry. South Africans were confronted with having to take rights seriously. This article assesses the major legal changes wrought through the right to equality and human dignity and argues that the reasoning, conclusion and consequences of the Fourie judgment was positive for the country as it taught important lessons about the supremacy of the Constitution, the constraints upon majoritarianism, respect for those differently situated and the consequences of taking rights seriously.